EVALUATION OF THE EFFECTIVENESS OF ACTION LEARNING IN AGRIPRENEURSHIP TRAINING IN OSUN STATE, NIGERIA - Ojubanire, O. A. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2018)
This study aimed at evaluating the effectiveness of action learning in agripreneurship training in Osun State. The specific objectives of the study were to determine the effect of action learning program on individual participant, assess the suitability of Practical Entrepreneurship Teaching Engagement (PETE) model to agripreneurship training program, identify success factors for action learning program in agripreneurship and assess the effectiveness of the training program. Simple random sampling technique was used to select a total of 169 respondents from a population of 300 selected FADAMA agripreneur applicants in Osun State. Structured questionnaire was used to collect data which were analysed using frequency counts, percentages and mean. The hypothesis was tested using correlation. The findings revealed that majority (74.0%) of the respondents were male, the mean age of the respondents was 30±3.32 years, 74.0 percent had either Bachelors’ degree or Higher National Diploma, 91.1 percent were experienced agripreneurs and 43.2 percent specialized in livestock production. With a grand mean of 3.37 and 2.68, the findings showed that action learning had much benefits to individuals and the PETE model is suitable for agripreneurship training respectively and 66.3 percent had their expectations from the training largely met. The correlation analysis showed that there is a positive and significant relationship between highly skilled facilitators or coaches (r = 0.147, p = 0.046*), well-coordinated self-directed team process (r = 0.243, p = 0.001*), effective team presentations (r = 0.249, p = 0.001*), support of top decision makers (r = 0.158, p = 0.032*), implementation and application of lesson objectives (r = 0.352, p = 0.000*) and the effectiveness of the training program. Based on the findings, it was concluded that action learning approach is effective in the delivery of agripreneurship training and the PETE model is also a suitable approach. It is recommended that policy makers adopt the PETE model and action learning approach in the delivery of entrepreneurship trainings.